2017
DOI: 10.3389/fphys.2017.00429
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNA Contribution to Thoracic and Abdominal Aortic Aneurysm Disease Development and Progression

Abstract: Multiple research groups have started to uncover the complex genetic and epigenetic machinery necessary to maintain cardiovascular homeostasis. In particular, the key contribution of non-coding RNAs (ncRNAs) in regulating gene expression has recently received great attention. Aneurysms in varying locations of the aorta are defined as permanent dilations, predisposing to the fatal consequence of rupture. The characteristic pathology of an aneurysm is characterized by progressive vessel wall dilation, promoted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 111 publications
(125 reference statements)
3
47
0
7
Order By: Relevance
“…A true aneurysm is defined as a permanent dilatation of the vessel wall, involving all layers. Enlargement > 1.5 times the expected diameter is considered an aneurysm [1]. Close to 90% of aortic aneurysms (AAs) are found in the abdominal aorta, where the typical clinical diameter threshold for an aneurysm is 30 mm, although individual anatomy may vary, and women can have smaller baseline diameters [2].…”
Section: Aortic Aneurysm Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A true aneurysm is defined as a permanent dilatation of the vessel wall, involving all layers. Enlargement > 1.5 times the expected diameter is considered an aneurysm [1]. Close to 90% of aortic aneurysms (AAs) are found in the abdominal aorta, where the typical clinical diameter threshold for an aneurysm is 30 mm, although individual anatomy may vary, and women can have smaller baseline diameters [2].…”
Section: Aortic Aneurysm Diseasementioning
confidence: 99%
“…MiRNAs have been extensively studied over the past 15 years. Their roles in regulating fundamental mechanisms of vascular disease development in general, and AA in particular, have suggested them as both promising therapeutic targets, and measurable biomarkers of disease progression [1,15,16]. Several miRNA-based clinical trials have been initiated [17,18].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Furthermore, various miRNAs have been established to be involved in the cell fates of vascular SMCs and in AAA ( Table 2) (60,68,74). However, the evidence on miRNA species involvement in the inflammatory processes driving AAA disease is limited.…”
Section: Neutrophil Leukocytesmentioning
confidence: 99%
“…34) Several clinical studies have demonstrated the altered miRNA expression in both human AAA wall and serum samples. 28,[35][36][37][38][39] Regulation of these miRNA via antagomirs or miRNA-mimics induces a potent therapeutic effect on experimental AAA formation. Silencing the expression of miRNA-29b, -155, -181b, and -712 using antagomirs inhibited elastase or Ang II-induced AAA expansion in a mouse model.…”
Section: Small Interfering Rna and Micrornamentioning
confidence: 99%